2012
DOI: 10.1007/s00415-012-6520-8
|View full text |Cite
|
Sign up to set email alerts
|

Interest of CSF biomarker analysis in possible cerebral amyloid angiopathy cases defined by the modified Boston criteria

Abstract: According to the modified Boston criteria, cerebral amyloid angiopathy (CAA) can present with lobar hematoma (LH) or superficial siderosis (SS). Recently, decreased CSF β-amyloid peptide 40 and 42 (Aβ40; Aβ42) and increased total and phosphorylated tau (t-tau; p-tau) concentrations have been described in CAA presenting with LH. Our aim was to analyze CSF biomarkers as a diagnostic tool for CAA according to the modified Boston criteria. We prospectively included patients with possible or probable CAA according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
45
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 13 publications
12
45
2
1
Order By: Relevance
“…21 Two previous studies in patients with sporadic CAA also demonstrated decreased CSF Ab 40 and Ab 42 levels. 10,11 However, in this study, the reduction in Ab 40 and Ab 42 was more pronounced, most likely because of the more severe phenotype of HCHWA-D. 22 Reduction in both CSF Ab 40 and 8 Our data hinted at the possibility that presymptomatic patients had relatively greater reductions in Ab 42 (55% of control values) than Ab 40 (75% of control values; figure 1 and table 2). This observation (which will require larger numbers of participants to confirm) likely relates to reports that in the process of Ab accumulation in the vessel wall, Ab 42 deposits earlier than Ab 40 .…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…21 Two previous studies in patients with sporadic CAA also demonstrated decreased CSF Ab 40 and Ab 42 levels. 10,11 However, in this study, the reduction in Ab 40 and Ab 42 was more pronounced, most likely because of the more severe phenotype of HCHWA-D. 22 Reduction in both CSF Ab 40 and 8 Our data hinted at the possibility that presymptomatic patients had relatively greater reductions in Ab 42 (55% of control values) than Ab 40 (75% of control values; figure 1 and table 2). This observation (which will require larger numbers of participants to confirm) likely relates to reports that in the process of Ab accumulation in the vessel wall, Ab 42 deposits earlier than Ab 40 .…”
mentioning
confidence: 50%
“…9 In patients with sCAA with advanced vascular damage, decreased CSF Ab 42 and Ab 40 and mildly elevated t-tau and p-tau concentrations have been found. 10,11 We aimed to find biomarkers of the earliest, potentially reversible phases of CAA. We investigated whether altered CSF levels of Ab and tau species are detectable in presymptomatic and symptomatic hereditary CAA mutation carriers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations of these criteria with post-mortem neuropathological findings indicate that the diagnosis of probable CAA-related hemorrhage can be made intra vitam with high accuracy [102]-[105]. In addition to the presence of superficial siderosis, cerebral microbleeds, cortical microinfarcts, and hypointensities in MRI images [106]-[109], the use of Pittsburgh Compound-B (PiB)-positron emission tomography (PET) is useful in detecting CAA intra vitam [110],[111], and a significant decrease of both Aβ-40 and Aβ-42 in cerebrospinal fluid (CSF) may prove useful in the diagnosis of CAA [112],[113], while in AD, Aβ-42 but not Aβ-40 are significantly decreased [114]. …”
Section: Reviewmentioning
confidence: 99%
“…Second, we did not investigate Apo E genotype, which influences the spatial distribution of CMBs (Loehrer et al., 2014). Finally, we did not examine useful biomarkers for vascular amyloid deposition, including amyloid imaging and Aβ 40 and Aβ 42 values in cerebrospinal fluid (Dierksen et al., 2010; Renald et al., 2012). However, we think that these data are an essential first step to understanding the clinical implications of differences between SL‐CMBs and M‐CMBs.…”
Section: Discussionmentioning
confidence: 99%